Gamifying Interprofessional Education: Development of the 'My Medicine E-Matching Card' Innovation - Elsye Maria Rosa; Sri Sundari; Galuh Suryandari; Erna Rochmawati; Sabtanti Harimurti; Wiwik Kusumawati; Farid Suryanto (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2025)
Introduction: Interprofessional education (IPE) is essential for equipping healthcare students with the competencies required for effective collaborative and patient-centered care. Traditional IPE methods, however, often lack interactivity and fail to simulate authentic clinical dynamics. Objective: This study aimed to design and evaluate the My Medicine E-Matching Card, a gamified digital platform intended to enhance IPE through interactive, case-based learning and foster collaboration among students of multiple health professions. Methods: A qualitative case study approach was employed involving 20 IPE lecturers from nursing, medicine, pharmacy, and dentistry programs at Universitas Muhammadiyah Yogyakarta. Data were collected through focus group discussions (FGDs) and analyzed using thematic analysis to guide the development of the application's features. Results: The analysis identified three core themes: the need for clear role delineation, interactive clinical case simulations, and mechanisms for real-time interdisciplinary collaboration. These themes were integrated into the app design. Lecturers noted improved student engagement, enhanced collaborative decision-making, and reduced hierarchical barriers. Key features of the application included customizable clinical scenarios, asynchronous learning access, and structured feedback tools. Conclusion: The My Medicine E-Matching Card demonstrates promise in advancing interprofessional learning by integrating gamification into IPE. By simulating real-life clinical encounters in a digital environment, the platform cultivates teamwork, communication, and clinical reasoning skills. Further longitudinal studies are warranted to assess its educational impact and scalability across institutions.